CLOTHING FUNCTIONS AND QUALITY REQUIREMENTS: FROM PHYSICAL TO DIGITAL - MYTSA, VIKTORIIA; DOMBROVSKA, OKSANA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This study examines the need to improve clothing functions and quality requirements, moving from traditional physical clothing to innovative digital fashion. In the era of digitalization and Generation Z's preference for online self-expression, clothing transcends its classical roles of protection and aesthetic appeal. It emerges as a tool for social identity, cultural communication, and even psychological resilience. The study highlights a growing demand for clothing that integrates physical and digital aspects, addressing the dual expectations of consumers in real and virtual environments. While physical clothing focuses on comfort, protection, and sustainability, digital clothing emphasizes realism, interactivity, and compatibility with augmented reality (AR) and virtual reality (VR) technologies. Innovations such as virtual try-ons, 3D modeling, and NFTs are reshaping traditional design, production, and consumption paradigms in the fashion industry.The analysis reveals a pressing need for rethinking clothing functions and quality standards. Current criteria often overlook digital garments' unique requirements, such as high-resolution textures, platform compatibility, and computational efficiency. The study also delves into the ecological benefits of digital fashion, which minimizes material waste and carbon footprints, aligning with global sustainability goals By developing a comprehensive framework for assessing the functions and quality of both physical and digital clothing, this research contributes to bridging the gap between traditional fashion and technological innovation, fostering a deeper understanding of how these domains intersect. It underscores the importance of integrating sustainable practices with cutting-edge technologies to meet the dynamic needs of modern consumers, drive industry-wide transformation, and redefine the future of the fashion industry through innovative and inclusive solutions.
Keywords: physical clothing; digital clothing; functions of clothing; requirements for clothing; digitalization